2015
DOI: 10.1063/1.4915142
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational dynamics of 3D HOCl above dissociation

Abstract: We explore the classical vibrational dynamics of the HOCl molecule for energies above the dissociation energy of the molecule. Above dissociation, we find that the classical dynamics is dominated by an invariant manifold which appears to stabilize two periodic orbits at energies significantly above the dissociation energy. These stable periodic orbits can hold a large number of quantum states and likely can support a significant quasibound state of the molecule, well above the dissociation energy. The classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…An alternative cause for the persistence might be a discrete symmetry. For two examples of the use of such surfaces see [30,31].…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…An alternative cause for the persistence might be a discrete symmetry. For two examples of the use of such surfaces see [30,31].…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…It has been suggested that it can play a role in the internal dynamics of molecules [14,51]. It has been observed recently in the dynamics of periodically kicked spin systems [52].…”
Section: Discussionmentioning
confidence: 97%